Sculpting the Blender Way : Explore Blender's 3D Sculpting Workflows and Latest Features, Including Face Sets, Mesh Filters, and the Cloth Brush. - Greer, Xury (Packt Publishing, Limited, 2022)
Get started with the latest sculpting features in Blender 3D and learn key sculpting workflows such as Dynotopo, Voxel Remesher, QuadriFlow, and Multiresolution Key Features Use Blender's core sculpting workflows: basic sculpting, Dynotopo, Voxel Remesher, QuadriFlow, and Multiresolution Learn how to use and customize Blender's sculpting brushes to create fantastic art effortlessly Explore common techniques in Blender 3.0 for creating facial features, clothing, accessories, and more Book Description Blender 3D is a free and open source program that can be used for every part of the 3D production pipeline. It has several robust feature sets for creating 3D art that have contributed to its rising popularity in the last few years. Sculpting is perhaps the most enjoyable and artistic method for creating 3D art as it relies less on technical knowledge and focuses on artistic brushes. The latest release of Blender makes the sculpting feature set more powerful than ever, so now is an excellent time to learn it! This book covers the expansive list of features in the Blender 2.93 LTS release, as well as the exciting all-new Blender 3.0 release. This book will be an excellent resource for professionals who need a production-ready long-term support release of the software, as well as hobbyists looking for a cutting-edge experience. Sculpting the Blender Way will demonstrate how to navigate Blender's user interface and take you through the core workflows. You'll gain a detailed understanding of how the sculpting features work, including basic sculpting, Dyntopo, the Voxel Remesher, QuadriFlow, and Multiresolution. This Blender book will cover a wide range of brushes, as well as all of the latest additions to the sculpting feature set, such as Face Sets, Mesh Filters, and the Cloth brush. You'll learn how to customize these brushes and features to create fantastic 3D sculptures that you can share with the ever-growing Blender community. By the end of this book, you'll have gained a complete understanding of the core sculpting workflows and be able to use Blender to bring your digital characters to life. What you will learn Configure your graphics tablet for use in 3D sculpting Set up Blender's user interface for sculpting Understand the core sculpting workflows Get the hang of using Blender's basic sculpting brushes Customize brushes for more advanced workflows Explore high-resolution details with brush alphas and Multiresolution Try out the all-new Cloth brush Render your finished artwork for your portfolio Who this book is for This book is for artists who want to get started with the exciting new sculpting features in Blender 3D. Whether you have experience using ZBrush or traditional sculpting, or are completely new to sculpting, this book will have something new for you to learn. Prior experience with Blender or other 3D software may be helpful but is not required. However, a graphics tablet from Wacom, XP-Pen, or Huion is highly recommended to be able to follow along the concepts and examples covered in the book.